2012
DOI: 10.1093/mp/ssr087
|View full text |Cite
|
Sign up to set email alerts
|

The Jasmonate-Responsive AP2/ERF Transcription Factors AaERF1 and AaERF2 Positively Regulate Artemisinin Biosynthesis in Artemisia annua L.

Abstract: Plants of Artemisia annua produce artemisinin, a sesquiterpene lactone widely used in malaria treatment. Amorpha-4,11-diene synthase (ADS), a sesquiterpene synthase, and CYP71AV1, a P450 monooxygenase, are two key enzymes of the artemisinin biosynthesis pathway. Accumulation of artemisinin can be induced by the phytohormone jasmonate (JA). Here, we report the characterization of two JA-responsive AP2 family transcription factors--AaERF1 and AaERF2--from A. annua L. Both genes were highly expressed in infloresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
310
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(321 citation statements)
references
References 74 publications
8
310
0
3
Order By: Relevance
“…Few MeJA up-regulated transcripts are the putative transcriptional regulators of MeJA responses in sweet basil (Supplemental Table S3). The APETALA2/ERF and WRKY transcription factors were previously shown as regulators of secondary metabolite biosynthesis in plants in response to MeJA (Yu et al, 2012;Mishra et al, 2013), suggesting their possible involvement in the regulation of secondary metabolite biosynthesis in sweet basil. Lectins, callose synthase, and thaumatin-like proteins that presumably do not have any role in secondary metabolite accumulation were also identified among the MeJA upregulated transcripts (Supplemental Table S4).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Few MeJA up-regulated transcripts are the putative transcriptional regulators of MeJA responses in sweet basil (Supplemental Table S3). The APETALA2/ERF and WRKY transcription factors were previously shown as regulators of secondary metabolite biosynthesis in plants in response to MeJA (Yu et al, 2012;Mishra et al, 2013), suggesting their possible involvement in the regulation of secondary metabolite biosynthesis in sweet basil. Lectins, callose synthase, and thaumatin-like proteins that presumably do not have any role in secondary metabolite accumulation were also identified among the MeJA upregulated transcripts (Supplemental Table S4).…”
Section: Discussionmentioning
confidence: 98%
“…When plants experience various biotic and abiotic stresses, biosynthesis of the secondary metabolites is triggered that helps plants adapt to the challenging environment (Gershenzon and Dudareva, 2007;Hartmann, 2007;Reichling, 2010). Consequently, transcript and metabolite profiling of stress/elicitor-treated plants or cell cultures represents a powerful approach to determine gene function in the biosynthesis of the secondary metabolites (Aerts et al, 1994;Goossens et al, 2003;Suzuki et al, 2005;Zhao et al, 2005;Naoumkina et al, 2008;De Geyter et al, 2012;Lenka et al, 2012;Yu et al, 2012;Ee et al, 2013;Mishra et al, 2013;Sun et al, 2013).…”
mentioning
confidence: 99%
“…In A. annua, two JA-responsive AP2 family TFs and a MYC-type bHLH TF have been identified as activators of the expression of genes encoding the sesquiterpene synthase and P450 essential for the production of the antimalaria compound artemisinin (Yu et al, 2012;Ji et al, 2014). In Arabidopsis, it has been observed that the bHLH TF MYC2 directly binds sesquiterpene synthase gene promoters, resulting in an elevated release of volatile sesquiterpenes (Hong et al, 2012).…”
Section: Members Of Clade Iva Of the Bhlh Family Activate Different Bmentioning
confidence: 99%
“…This strategy has been successfully applied to many cases of novel gene functional elucidation when using plant glandular trichomes as an experimental subject (Dai et al 2010;McDowell et al 2011;Schilmiller et al 2010b;van Bakel et al 2011). It is noteworthy that there are only a few studies that have focused on the genes related to glandular trichome development and the transcription factors that regulate trichome-specific biosynthesis pathways (Ma et al 2009;Spyropoulou et al 2014;Yu et al 2012). It is the same case in studying metabolite transportation of glandular trichomes (Choi et al 2012).…”
Section: Gene Discovery From Plant Glandular Trichomes Using System Bmentioning
confidence: 99%